KEDUDUKAN HUKUM BUMDES DAN POTENSI BUMDES DALAM PERTUMBUHAN EKONOMI MALUKU UTARA: Legal Standing Of Bumdes And Potential Of Bumdes In North Maluku Economic Growth - Lutfi Mubarok; Juan Malik Frederick Turpyn; Mubarok, Lutfi (Jurnal Hukum PRIORIS, 2023)
North Maluku, as a province with numerous villages scattered across various islands, possesses diverse natural potential yet still faces significant economic challenges. This research aims to analyze the potential of Village-Owned Enterprises (BUMDes) in supporting economic growth in North Maluku. The study employs a mixed methods approach by combining quantitative and qualitative data. Primary data were obtained through direct surveys and interviews with BUMDes stakeholders, while secondary data were collected from relevant sources. The findings indicate that the legal status of BUMDes as a legal entity is clarified through the Job Creation Law and is a new entity whose position is equivalent to a Limited Liability Company (PT) comparable to state-owned enterprises (BUMN) at the national level and regional-owned enterprises (BUMD) at the local level, then BUMDes have significant potential to support economic growth in North Maluku. In the economic aspect, BUMDes play a role in the development of sectors such as agriculture, fisheries, tourism, and local handicrafts. BUMDes also provide employment opportunities for village residents, contributing to increased income and local well-being. This research offers a clearer understanding of the potential of BUMDes in North Maluku's economic growth and serves as a foundation for further strategy development to maximize the contribution of BUMDes in enhancing the welfare of rural communities and driving regional economic growth. Keywords: BUMDes Potential, Growth, North Maluku, Economy